Direct or Indirect Exporting? The Joint Influence of Gender and Immigration Background on Export Strategies of Canadian SMEs - Wang, Xiaojing; Morgan, Horatio M.; Ye, Yu Wei (Journal of Comparative International Management)

(untitled) (Management Futures, 2024)
Given the challenges women-owned small and medium-sized enterprises (SMEs) face in global markets, we investigate the effects of gender and immigrant background on their direct versus indirect export strategies. Drawing on insights from social capital theory, our analysis consists of a sample of 109 Canadian SMEs. We found that although women-majority-owned SMEs are less likely to export directly compared to their men-majority-owned counterparts, women owners with an immigrant background have the potential to overcome network-related barriers, thus weakening the negative effect of gender on direct exporting. These results point to the significance of having access to international networks and the necessity to leverage this linkage to support the direct exporting approach for women-majority-owned SMEs. Our research guides SME owners and managers with global aspirations. We suggest policymakers develop initiatives to encourage women owners to identify, build, and cultivate international business relationships and improve the design and implementation of policies targeted at immigrant export businesses.